Optociliary Shunt Vessel: An Ancillary Ophthalmic Sign Harbingering Optic Nerve Sheath Meningioma - Thapa, Bikram Bahadur; Singh, Sweta; Basnet, Rakshya; Piya, Saurav (Nepal Journal of Neuroscience, 2019)
A 61-year-old male presented with gradual loss of vision in his right eye for one year at neuro ophthalmology clinic. On clinical examination, his visual acuity was perception of light and intraocular pressure was 12 mm of Hg in right eye. Also, there was relative afferent pupillary defect in the right eye. Fund us examination showed per papillary atrophy, temporal pallor in optic disc with dilated and tortuous optociliary shunt vessels in right eye. Presence of optociliary shunt, visual loss, relative afferent pupillary defect and optic atrophyopt us for further evaluation by visual field and magnetic resonance imaging. Visual field showed unilateral blindness suggesting lesion of optic nerve. Magnetic resonance imaging brain revealed optic nerve sheath meningioma.